Automated synthesis of 18F radiolabelled indole containing Oncrasin-like molecules; a comparison of iodonium salts and boronic ester chemistry - Alexander F. McDonald; Yit Wooi Goh; Jonathan M. White; Andrew M. Scott; Uwe Ackermann (SpringerOpen, 2020)
Abstract Background Oncrasin-1 is a small molecule which was identified from a screen of KRAS mutant cancer cells and has shown specificity for KRAS mutant cell killing. We aimed to develop a radiolabelled form of Oncrasin-1 to enable in-vivo imaging of mutant KRAS expression in malignant tumours. This work outlines the synthesis of 3 fluorinated derivatives and development of iodonium salt and boronic ester precursors for radiolabelling with the 18F isotope. Results In our hands, synthesis of iodonium salts were not easily accessible due to the 3-carbaldehyde indole structure being preferentially oxidized by conditions required for iodonium salt formation, rather than benzyl iodide. Synthesis and radiolabelling of boronic acid pinacol ester precursors were successful, with the products being obtained in yields of 10.76% ± 0.96% (n = 5), 14.7% ±8.58% (n = 3) and 14.92% ±3.9% (n = 3) for 18F KAM001, 18F KAM002 and 18F KAM003 respectively, with radiochemical purity of greater than 99%. Conclusions The successful synthesis of these tracers has been undertaken utilizing boronic ester radio-fluorination methods and will allow for investigation of Oncrasin based molecules as potential diagnostics for cancers expressing mutant KRAS protein.